SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA ANALOG PIRAZOLIN TURUNAN 3’BROMOKALKON INTI NAFTALEN - Sriatun Sadiah; Yuharmen '; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Analog compound  of  3'bromochalcone  pyrazoline  derivative  5-  (3-bromofenil)  -3-(naphthalene-2-yl)  -1-fenill-4.5-dihydro-1H pirazol (PP2) was  synthesized through nucleophilic addition reactions using glacial acetic acid catalyst under microwave radiation. PP2  compound  was obtained as yellow crystal  with yield  of  77.73%.  The purity of pyrazoline analog coumpound has been tested using TLC  observation, determination of melting point,  HPLC  analysis  and characterized by UV spectroscopy, IR spectroscopy, Mass spectroscopy and NMR spectroscopy. Antibacterial test conducted by the agar diffusion method with concentration of 10 μg/disk dan 30 μg/disk against Gram-positive bacteria, B. subtilis and S. aureus, and Gram-negative bacteria, E. coli and S. typhi. PP2  compound  showed that there was a low antibacterial activity. However, the inhibition of PP2 against Gram-positive bacteria is greater than  that of Gram-negative bacteria.